(3EfHGA GdZeQ HCHfGA GdYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdVYja CMeO (B,,,(3Hf MLQ GdYSbdGfi gPG JYdjb MOK ajg MhGOK GdReGf s
(3BNQgG (B:s
(3ef LeGd GdOjf GdfGUQ bHdg abJdg hcGfJ dg eYQaI hgeI YGdjg Je BNQ GdeLdO GdChd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B35 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO GdKGdK (B(1/ 2942) s
Keywords: (3GdJGQjNs